Sophisticated Rebels / The Political Culture of European Dissent - 1968-1987 - Hughes H. Stuart (Harvard University Press, 1990)
A vivid picture of people who ''had in common a resolute moral sense''. Preface, ''The Moral Equivalent of War'', The Parisian Scene: The Return of the Novel, The Torment of a Foreign Underclass, The Reassertion of Historic Cultures: The Case of Wales, The Pope and His Antagonists, The Sixteen Monts of Solidarity, The Frustration of Soviet Dissent, Democratic Socialism: North and South, Notes, Index.